Power and energy [Technology 2000 analysis and forecast]. - Sweet, W.
Partly because it is the turn of the Century and the Millennium, and partly because the huge challenges facing the electric power industry cry out for bold new approaches, a number of influential organizations have formulated sweeping plans for the world's energy future. Ironically, at just the time these far-reaching roadmaps have been appearing, the US power system has been plagued by concrete, workaday problems that just as manifestly are not being adequately addressed. Over the last decade, the power system has been converted into a common carrier network; the vertically integrated utilities of tradition have been ?unbundled? into generators, distributors, and transmitters of electricity and much of the time-honored regulatory apparatus has been dismantled or weakened. From one point of view, the system looks to be separating Lear-like into a set of feuding baronies. Even as each proffers its own view of the situation and vies with the others- to impose or sell a preferred approach, none has the legal, political, or moral authority to do so
Keywords: USA; Common carrier network; Electric power industry; Technology analysis; Technology forecast; Vertically integrated utilities